"What If" analysis: Benefits of utilizing a "What If" analysis in excel. Issue 12 (18th June 2017) - Peltier, Corey
ABSTRACT: The "What If" analysis is applicablein research and heuristic situations that utilize statistical significance testing. One utility for the "What If" is in a pedagogical perspective; the "What If" analysis provides professors an interactive tool that visually represents examples of what statistical significance testing entails and the variables that affect the commonly misinterpreted pCALCULATED value. In order to develop a strong understanding of what affects the pCALCULATED value, the students tangibly manipulate data within the Excel sheet to create a visualize representation that explicitly demonstrates how variables affect the pCALCULATED value. The second utility is primarily applicable to researchers. "What If" analysis contributes to research in two ways: (1) a "What If" analysis can be run a priori to estimate the sample size a researcher may wish to use for his study; and (2) a "What If" analysis can be run a posteriori to aid in the interpretation of results. If used, the "What If" analysis provides researchers with another utility that enables them to conduct high-quality research and disseminate their results in an accurate manner.